Higher Education Management in Promoting the Implementation of Deep Learning in the Digital Age - Andriani Sariwardani; Abdul Halik; Rohimah Rohimah (Gestion Educativa, 2025)
The rapid advancement of digital technologies and policy reforms such as Indonesia’s Merdeka Belajar Kampus Merdeka initiative require higher education institutions to shift from content-oriented instruction to deep learning practices driven by student-centered pedagogy. This study analyzes the role of higher education management in promoting deep learning implementation in the digital era using a systematic narrative literature review approach. Academic literature and educational policy documents published between 2019 and 2024 were examined to identify institutional strategies, leadership roles, faculty capacity building, technological support, and quality assurance mechanisms. Findings reveal that successful deep learning implementation relies on transformational leadership, outcome-based curriculum design, authentic assessment, and digital learning infrastructure including LMS platforms, learning analytics, and collaborative learning systems. However, challenges persist in the form of limited faculty pedagogical readiness, variations in student learning cultures, digital access disparities, and administrative-oriented quality assurance systems. This study recommends strengthening teaching and learning centers, implementing continuous digital pedagogy training, expanding technological infrastructure, and enhancing industry partnerships to support experiential and interdisciplinary learning. The findings contribute to a comprehensive model of higher education management that fosters sustainable and systemic deep learning implementation in Indonesia.